2020
DOI: 10.1017/s1368980019004890
|View full text |Cite
|
Sign up to set email alerts
|

Changes in nutrition content and health claims post-implementation of regulation in Australia

Abstract: Objective:To determine whether there were changes in the prevalence or healthiness of products carrying claims post-implementation of Standard 1.2.7: Nutrition, Health and Related Claims in the Australia New Zealand Food Standards Code.Design:Observational survey of claims on food packages in three categories: non-alcoholic beverages, breakfast cereals and cereal bars. Nutrient profiling was applied to products to determine their eligibility to carry health claims under Standard 1.2.7. The Standard came into e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Such claims have also been criticised as being a marketing tool developed by food manufacturers to increase product sales, which has resulted in a general consumer distrust (Talati et al ., 2016; Stuthridge et al ., 2022). A number of studies have described health claims as being deceptive and misleading, particularly if the claim promotes a certain nutrient in a positive manner while failing to consider the substantial quantities of risk nutrients, such as added sugars, saturated fat and sodium, in the same product (Wellard-Cole et al ., 2020; Talati et al ., 2016; Manoj Hastak and Mazis, 2011; Lawrence et al ., 2017). Evidence suggests that nutrition and health claims can have a “health halo” effect whereby products that display nutrition and health claims, or more ambiguous statements such as a food being “natural” (Skubisz, 2017), are perceived to be healthier although the overall nutrient profile of the food product is poor (Wang et al ., 2016; Ikonen et al ., 2020; Anastasiou et al ., 2019; Kerr et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Such claims have also been criticised as being a marketing tool developed by food manufacturers to increase product sales, which has resulted in a general consumer distrust (Talati et al ., 2016; Stuthridge et al ., 2022). A number of studies have described health claims as being deceptive and misleading, particularly if the claim promotes a certain nutrient in a positive manner while failing to consider the substantial quantities of risk nutrients, such as added sugars, saturated fat and sodium, in the same product (Wellard-Cole et al ., 2020; Talati et al ., 2016; Manoj Hastak and Mazis, 2011; Lawrence et al ., 2017). Evidence suggests that nutrition and health claims can have a “health halo” effect whereby products that display nutrition and health claims, or more ambiguous statements such as a food being “natural” (Skubisz, 2017), are perceived to be healthier although the overall nutrient profile of the food product is poor (Wang et al ., 2016; Ikonen et al ., 2020; Anastasiou et al ., 2019; Kerr et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In this earlier study, Pulker et al gathered data from both websites and physical stores and found only 59% of products (ultra-processed foods including breakfast cereals, confectionary, and snacks) carried nutrition or health claims. A Sydney-based supermarkets study by Wellard-Cole et al [ 22 ], auditing claims on non-alcoholic beverages, cereal bars and breakfast cereals in 2011 and again in 2016, confirmed that change was happening (increasing from 67% of audited products in 2011, to 76% in 2016, p < 0.001). Of the 1737 products audited in 2016, 76% carried at least one claim, the majority (82%) being content claims [ 22 ].…”
Section: How Do Regulators and Manufacturers Work With Nandhc?mentioning
confidence: 99%
“…A Sydney-based supermarkets study by Wellard-Cole et al [ 22 ], auditing claims on non-alcoholic beverages, cereal bars and breakfast cereals in 2011 and again in 2016, confirmed that change was happening (increasing from 67% of audited products in 2011, to 76% in 2016, p < 0.001). Of the 1737 products audited in 2016, 76% carried at least one claim, the majority (82%) being content claims [ 22 ]. Thus, there appeared to be a high prevalence of claims on foods in Australian supermarkets, with increasing use over time, suggesting a high acceptance of the system by manufacturers.…”
Section: How Do Regulators and Manufacturers Work With Nandhc?mentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure consumers are not given misleading information, many countries have regulated the use of health claims on foods (de Boer & Bast, 2015a). The use of such claims on food labeling is well documented in the European Union (EU) (Hieke et al, 2016;Kaur et al, 2016a;Kaur et al, 2016b;Lalor, Kennedy, Flynn, & Wall, 2010;Lopéz-Galán & De-Magistris, 2017;Pravst & Kušar, 2015;Storcksdieck genannt Bonsmann et al, 2010), Canada (Sacco, Sumanac, & Tarasuk, 2013;Schermel, Emrich, Arcand, Wong, & L'Abbe, 2013), the USA (Brecher, Bender, Wilkening, McCabe, & Anderson, 2000;Colby, Johnson, Scheett, & Hoverson, 2010), and Australia and New Zealand (Al-Ani, Devi, Eyles, Swinburn, & Vandevijvere, 2016;Devi et al, 2014;Hughes, Wellard, Lin, Suen, & Chapman, 2013;Ni Mhurchu et al, 2016;Walker, Woods, Rickard, & Wong, 2008;Wellard-Cole, Li, Tse, Watson, & Hughes, 2020;Williams et al, 2003Williams et al, , 2006. Health claims on food products offer a direct communication channel between food producers and consumers at the point of purchase to inform about the health-related benefits a product can offer.…”
Section: Introductionmentioning
confidence: 99%